The chronicles of Narnia [videorecording (DVD)] - Fox, Marilyn; Kirby, Alex; Dempsey, Richard; Cook, Sophie, 1974-; Scott, Jonathan R.; Lewis, C. S. (Clive Staples), 1898-1963 (2 Entertain, 2010)
After escaping the London blitz, the Pevensie siblings discover a magical world which tests their bravery and loyalty to each other.